A case of a vaginal Brenner tumor without a gland mimicking a borderline tumor: unusual morphology and diagnostic pitfalls. Issue 8 (August 2020) - Zhang, Qin; Tian, Can; Wang, Kun; Xin, Qi; Shen, Yan; Zhang, Chuan-shan; Ma, Zhe
Brenner tumor is a rare neoplasm of the vagina. This tumor is diagnosed according to the criteria of ovarian tumors. We report here a 64-year-old postmenopausal woman with a 2.0-cm sessile vaginal polyp for 9 years. Microscopic examination showed unusual features of no gland appearing in the tumor, but the other two characteristic components of transitional islands and dense fibrous stroma were observed. The tumor was diagnosed as a vaginal Brenner tumor on the basis of the definition proposed by the World Health Organization classification of female reproductive organ tumors. In our case, part of the epithelial nests of the Brenner tumor showed basaloid cell differentiation with peripheral palisading, and irregular papillary hyperplasia was observed around the epithelial nests similar to a borderline tumor. However, no mitotic activity or nuclear atypia was present in either the epithelial or stromal components. The presence of epithelial nests requires attention in the medical history of the patient. Our patient did not have a history of primary urothelial carcinoma. Our patient's benign vaginal Brenner tumor with different morphological characteristics supports the current notion that Walthard nests might act as possible precursor lesions.